Agronomic application effects of organic wastes on a squash crop production - Graciela Pellejero; Jonathan Menéndez; Julieta Palacios; Gabriela Aschkar; Francisco J. Garcia-Navarro; Juan M. Trujillo-Gonzalez; Juan L. Chacon-Vozmediano; Raimundo Jimenez-Ballesta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The objective of the study was to evaluate the application effects of different doses of onion residue mixed with bovine manure compost as an organic fertilizer on a hybrid Tetsukabuto squash crop cultivated in a field.Method The experimental design required randomly dividing blocks with three replicates. The experiments were designed with different dose combinations in experimental units (4 m wide x 8 m long deep). There were three treatments: organic fertilization (two compost doses 6 and 8 kg m-2); mineral fertilization (45 kg N ha-1 urea), unfertilized control. The number of leaves, main guide length per plant and dry matter were determined.Results The results obtained during the first 15-day sampling showed significant differences (p <0.05) in both number of leaves and main guide length per plant between the treatments with compost doses and the control without fertilization. The treatment with the compost dose of 6 kgm-2 produced the highest effect. . Furthermore, there were no significant differences (p <0.05) among the three treatments in both the number of leaves and main guide length per plant during the second post-sowing 60-day sampling, as well as in the dry matter during the first sampling. During the second sampling, the percentage of dry matter in the control differed significantly from the two fertilized treatments.Conclusion Compost of onion residue mixed with bovine manure can be applied as an organic fertilizer with similar positive effects to mineral fertilization in the first squash crop implantation stage.